1999
DOI: 10.1046/j.1365-2958.1999.01634.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of polyamines and trypanothione resulting from overexpression of the ornithine decarboxylase gene in arsenite‐resistant Leishmania

Abstract: SummaryThe levels of trypanothione, a glutathione±spermidine conjugate, are increased in the protozoan parasite Leishmania selected for resistance to the heavy metal arsenite. The levels of putrescine and spermidine were increased in resistant mutants. This increase is mediated by overexpression of ornithine decarboxylase (ODC), the rate-limiting enzyme in polyamine biosynthesis. Gene overexpression is generally mediated by gene ampli®cation in Leishmania but, here, the mRNA and the enzymatic activity of ODC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
106
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 64 publications
2
106
0
2
Order By: Relevance
“…Therefore, we explored other mechanisms that could have led to increased levels of these proteins. Although occurring less frequently than gene amplification, RNA overexpression without gene amplification has been observed in drug-resistant Leishmania (30). Previously, DNA microarray data and northern hybridization experiments had indicated Table II.…”
Section: Analysis Of the Initial Responses Of L Major To Mtx By Two-mentioning
confidence: 99%
“…Therefore, we explored other mechanisms that could have led to increased levels of these proteins. Although occurring less frequently than gene amplification, RNA overexpression without gene amplification has been observed in drug-resistant Leishmania (30). Previously, DNA microarray data and northern hybridization experiments had indicated Table II.…”
Section: Analysis Of the Initial Responses Of L Major To Mtx By Two-mentioning
confidence: 99%
“…A considerable body of evidence implicates trypanothione and glutathione (␥-L-glutamyl-L-cysteinylglycine) in the efflux-mediated detoxification of Sb III and other heavy metals in the laboratory-induced resistant lines of Leishmania (18,19). Overexpression of ␥-glutamylcysteine synthetase (20) and ornithine decarboxylase (21) (the rate-limiting steps in the biosynthesis of the respective GSH and spermidine moieties of T[SH] 2 ) and overexpression of PgpA (20,22) (an intracellular metal-thiol transporter) have all been demonstrated to play a role in resistance. However, there are no reports implicating these effects in the mode of action of Sb III .…”
mentioning
confidence: 99%
“…Ornithine decarboxylase (ODC) and γ-glutamylcysteine synthetase (γ-GCS) are the two rate-limiting enzymes present in the polyamine and glutathione biosynthetic pathways, respectively (Haimeur et al, 1999).…”
Section: Antimonial Mechanism Of Action and Resistancementioning
confidence: 99%
“…Reversion of metal resistance can be achieved by downregulation of TSH levels by specific γ-GCS or ODC inhibitors, such as L-buthionine-(SR)-sulphoxime (BSO) and DL-α-difluor-o-methylornithine (DFMO), respectively (Haimeur et al, 1999). Grondin et al (1993 reported an increase in thiol levels as a result of an overexpression of either ODC or γ-GCS in L. tarentolae wild-type cells.…”
Section: Antimonial Mechanism Of Action and Resistancementioning
confidence: 99%
See 1 more Smart Citation